Peculiarities of formation of recreational land use in the suburban zone of the megapolis - Butenko, E.; Vintselevych, A. (Land Management, Cadastre and Land Monitoring, 2021)
The article highlights the scientific principles of the formation of environmental land use in Ukraine. The components of suburban areas of megacities and the process of their development in modern society are studied. The article reflects the impact of urbanization on land use and the environment. Emphasis is placed on the fact that the development of urbanization is accompanied by the disappearance of valuable natural and recreational complexes, the loss of cultural and historical heritage, increasing social tensions.The study was carried out on the basis of statistical and analytical data of the Ministry of Environmental Protection and Natural Resources of Ukraine, the State Geocadastre of Ukraine, the State Statistics Service of Ukraine, the Ministry of Economy of Ukraine, materials of scientific conferences, seminars, the author’s own calculations.The article substantiates the need to create recreational land use in the suburban area of the metropolis. The conceptual apparatus in terms of interpretation of the concepts "recreational areas", "recreational land use", "recreational lands" is studied. An assessment of the peculiarities of the creation, use and maintenance of recreational land use in the suburban area of the metropolis. The procedure of formation of lands of recreational purpose, significance of these territories is revealed.As a result, it is established that the most important problems of recreational land use in Ukraine are ensuring high quality recreation, expanding the diversity of opportunities for recreational lands and resources closely related to them, meeting people’s needs to communicate with wildlife and restoring public health. However, the radical transformation of landscapes and the large-scale development of urbanization have led to a decrease in the recreational value of landscapes and thus to the formation of recreational areas on lands unsuitable for other economic uses. All this negatively affects the quality of recreation, the diversity of recreational activities and the ability to remain in the recreational sphere of landscapes that meet the needs of the population in recreation.Key words: recreational land use, suburban area of the metropolis, recreational territories, lands of recreational purpose.